The motivational effect of multicolored dental restoration on dental behavior of first preliminary school children. Issue 4 (19th June 2019) - Melebari, Lojain Abdulaziz; Attas, Seba Essam; Arafa, Abla
Abstract: Objectives: To assess the motivational effect of multi‐colored restoration on the anxiety level of pediatric patients at thedental clinic and its motivational effect on their oral hygiene status. Material and methods: A total of 30 participants. Results: Both groups revealed reduction in the anxiety level and improvement in their behavior at the dental office but did not reach significance. Plaque index showed a significant reduction per group and a near significance as compared between test groups. Conclusions: The use of the multicolored restoration could provide a potential advantage to improve the oral health status of children and might aid in enhancing their behavior at dental clinic particularly younger age groups.